Integrasi Teknologi Informasi dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Harjo Nawi; Nanik Herawati; Agus Yuliantoro (Universitas Muhammadiyah Sorong, 2025)
This research aims to analyze the integration of information technology in Indonesian language learning at the Inpres 18 Elementary School (SD) in Sorong Regency. With the increasing development of technology, the use of information technology in education has become very important to improve the quality of learning, especially in Indonesian language subjects. This research uses a qualitative approach with a case study method. Data was collected through interviews, observation and documentation involving teachers, students and school principals. The research results show that although information technology has begun to be introduced in learning, its use is still limited to the use of digital tools such as projectors and computers for presenting material. Apart from that, several obstacles faced include limited facilities and infrastructure, lack of training for teachers in using technology, and low levels of technology skills among students. This research suggests the need to increase training for teachers and provide adequate facilities to support the use of information technology in the Indonesian language learning process. It is hoped that with more optimal integration, Indonesian language learning in elementary schools can be more interesting, interactive and effective.